Os custos de produção como método de auxílio à tomada de decisão aplicado aos apicultores do Vale do Jaguari/RS - Perdoná, Igor Idalgo (2019)
The apiculture is a very importante activity in Brazil, being the South region the biggest honey producer, respon-sable for 37,2% from de total made in the country. In South Zone, the Rio Grande do Sul is the biggest Brazilian producer, responsable for 15,8% of the nacional product (IBGE, 2016). However, the apiculturist must look for explore the accounting of costs like fount of information breed, once the Manufacturing Costs comes following about new features of the economic system exerted by the globalization. In this sense, checked the importance in relation to management costs control in the agribusiness and the necessity in administrating rural enterprises, the present study proposes like major target map the Manufacturing Costs of the Vale do Jaguari/RS beekeeping chain, aiming a costs control method that be adapted to several apiculturists reality, also constitute control in-formation and allow analyses for taking-decisions. In front of this scene, the work with pioneer nature in this region studied operationally the Manufacturing Costs that envolves this segment. Through the Theoretical Fra-mework were rised and analysed publications in Apiculture, Costs Apiculture Management and Costs Production areas, to orient the research together the Apiculturists. Were applied 54 questionnaires in nine cities of this zone (Cacequi, Capão do Cipó, Jaguari, Mata, Nova Esperança do Sul, Santiago, São Francisco do Sul, São Vicente do Sul e Unistalda). The results showed in the search about the financial área were: 41% of the Apiculturists do not calculate the Manufacturing Costs and 50% use Thecnique and Economic Indicators to their taking-decision. In relation to the tecnology uses: just 19% of the Apiculturists utilize data processing inside the product mana-gement of honey. Based in this results, was built a costs management software to the free access created to Vale do Jaguari Apiculture actuality, that uses the Absorption Accounting and Variable Method, beyond Manufactu-ring Costs methodologies from the authors Dal Monte et al. (2010), Martin et al. (1998) and Matsunaga et al. (1976).